A First‐Principles Study of Electronic Structure of the Laves Phase MgZn2. Issue 11 (15th May 2013) - Andrae, Dirk; Paulus, Beate; Wedig, Ulrich; Jansen, Martin
Abstract The electronic structure of the intermetallic compound MgZn2, a prototypical Laves phase, was investigated by first‐principles calculations based on Kohn‐Sham density‐functional theory. A variety of six exchange‐correlation energy density functionals, from local density approximation to hybrid functionals, was used to fully optimize the crystal structure. Cell parameters and mass density calculated with the density functional parameterization by Perdew, Burke, and Ernzerhof (PBE) were found closest to their corresponding experimental values. The revised version of the functional, PBEsol, recommended for solid state applications, gave inferior results. The electronic structure was analysed in terms of band structure, density of states and electron density.